Inflammatory Mechanisms in Mediating Hearing Loss (Springer International Publishing, 2018)
The primary goal of this project is to describe our current understanding of the oxidant hypothesis of noise and drug-induced hearing loss and show how this process translates into cochlear inflammation. Basic cellular mechanisms underlying the contribution of oxidant stress to hearing loss will be explained and molecular pathways leading to inflammatory processes will be outlined. Several different aspects of the cochlear inflammatory process will be discussed in detail. These include the sources of inflammatory cells, chemokines, inflammatory cytokines and the roles of cochlear resident immune cells in mediating hearing loss. In addition, evidence for a robust cochlear-based steroid axis which is activated by cochlear stress and serves a protective system. The role of the strial vasculature networks which aid in maintenance of the blood-labyrinth barrier and control the entry of circulating immune cells into the cochlea will be described. Molecular pathways leading to activation of the local inflammatory process will be highlighted and otoprotective treatment options will be discussed. The relevance of certain clinically used anti-inflammatory interventions, such as trans-tympanic steroids and other drugs will also be discussed. Furthermore, we will examine recent patents focusing on the use of anti-inflammatory agents for the treatment of drug and noise-induced hearing loss. It is our hope that this book would provide a better understanding of the interaction of oxidative stress and inflammation in hearing loss. This book should provide basic information to scientists in the field of auditory research and to enlighten clinicians who treat patients with potentially ototoxic drugs.